Analysis of The Impact of Financial Performance on Company Value with Corporate Social Responsibility and Good Corporate Governance as Moderating Variables - Sulhan, Muhammad; Pratomo, Ahmad Sidi (MEC-J (Management and Economics Journal), 2020)
Today every company is trying to maximize the value of its company. Disclosure of company information is expected to be able to maximize the value of the company, including Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), Financial Performance of the Company. The purpose of this study is to find out that CSR and GCG as moderating variables can strengthen or weaken the significance of the effect of financial performance (profitability, size, leverage, slack resources, and institutional ownership) on company value. This type of research is explanatory research; the population in this study are all Pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). Determination of the sample is done using the purposive sampling method. Data analysis uses Moderated Regression Analysis (MRA) with the help of SPSS software. The results of this study indicate. First, Financial Performance profitability, size, leverage, and slack resources have a significant effect on company value in pharmaceutical companies. Second, CSR and GCG variables can strengthen the influence of Financial Performance that is proxied by profitability, size, leverage, slack resources, and institutional ownership of company value in pharmaceutical companies listed on the IDX.